TAFSIR FIKIH DALAM KHAZANAH PENAFSIRAN ALQURAN - Arif Zunzul Maizal (JURIS (Jurnal Ilmiah Syariah), 2020)
The interpretation of the Koran as a sacred text turns out to not escape subjectivity. This can be seen from the rapid development of interpretation which is influenced by the subjectivity or tendency of each mufassir. Jurisprudence between trends or patterns of interpretation is growing rapidly, so it requires in-depth discussion and study. Discussion about the nature of fiqh interpretation is done through library research on fiqh interpretation works, beginning with collecting related references then discussing with using descriptive, analytical and comparative methods. From these discussions, several conclusions were formulated. First; the attention of scholars to the interpretation of fiqh is very large, this is evident in the many books of fiqh interpretations, both in the form of interpretations of fiqh verses in a special way, interpretation of fiqh verses in a thematic manner and interpretation of fiqh verses together with other verses in one interpretation book. Second, the method of istinbath fiqh law greatly influences the method of fiqh interpretation, so that differences in fiqh interpretation follow the polarization of fiqh schools. Third, some jurisprudents of fiqh interpretation are trapped by the tendency of the school they follow so that fiqh interpretation becomes a justification tool for the existing fiqh opinion concept.